Predictors of Premature Rupture of Membranes among Pregnant Women in Rural Uganda: A Cross-Sectional Study at a Tertiary Teaching Hospital. (3rd March 2020) - Byonanuwe, Simon; Nzabandora, Emmanuel; Nyongozi, Baltazar; Pius, Theophilus; Ayebare, David Santson; Atuheire, Collins; Mugizi, Wilson; Nduwimana, Martin; Okello, Maxwell; Fajardo, Yarine; Ssebuufu, Robinson
Abstract : Background . Premature rupture of membranes (PROM) is a common condition in developed and developing countries and poses a serious threat to the maternal and fetal well-being if not properly managed. This study delineated the prevalence and predictors of PROM in the western part of Uganda so as to guide specific preventive measures. Methods . A cross-sectional study design was conducted in the months of September 2019 to November 2019. A total of 334 pregnant women above 28 weeks of gestation admitted at the maternity ward of KIU-TH were consecutively enrolled. Interviewer-administered questionnaires were used to obtain the data. Descriptive statistics followed by binary logistic regression were conducted. All data analyses were conducted using STATA 14.2. Results . Of the 334 pregnant women enrolled, the prevalence of PROM was found to be 13.8%. The significant independent predictors associated with lower odds of PROM were no history of urinary tract infection (UTI) in the month preceding enrollment into the study (aOR = 0.5, 95% CI: 0.22-0.69, p = 0.038 ) and gestational age of 37 weeks or more (aOR = 0.3, 95% CI: 0.14-0.71, p = 0.01 ) while history of 3 or more abortions (aOR = 13.1, 95% CI: 1.12-153.62, p = 0.05 ) was associated with higher likelihood of PROM. Conclusions . Majorly urinary tract infections, low gestational age, and abortions influence premature rupture of membranes among women. There is a great need for continuous screening and prompt treatment of pregnant women for UTI especially those with history of 3 or more abortions at less than 34 weeks of gestation.